EVALUATION OF IN-VITRO IMMUNOMODULATORY ACTIVITY OF AQUEOUS AND ETHANOLIC EXTRACT OF CAPPARIS MOONII - VANITA G.KANASE; DR.BRIJENDRA B.JAIN; DR.PRAMILA YADAV (International Journal of Pharma and Bio Sciences, 2013)
The present study was intended to evaluate the in-vitro immunomodulatory activity of aqueous and ethanolic extract of dried fruits of Capparis moonii Wight. Effect of both the extracts were evaluated at various concentrations (832 μg/ml to 6.5 μg/ml) for secretion of variouesmediators like nitric oxide, superoxide, lysosomal enzyme etc of isolated murine peritoneal macrophages. Both the extracts showed in-vitro phagocytic stimulation of, lysosomal enzyme and myeloperoxidase activity and nitric oxide in peritoneal mouse macrophages. In-vitro phagocytic index showed significant results and thus proving the need for confirmation through in-vivo studies.